N-Cadherin promotes cardiac regeneration by potentiating pro-mitotic β-Catenin signaling in cardiomyocytes - Yi-Wei Tsai; Yi-Shuan Tseng; Yu-Shuo Wu; Wei-Lun Song; Min-Yi You; Yun-Chia Hsu; Wen-Pin Chen; Wei-Han Huang; Jia-Ci Chng; Chai-Ling Lim; Ke-Hsuan Wei; Shih-Lei Ben Lai; et al. (Nature Communications)
Abstract Adult human hearts exhibit limited regenerative capacity. Post-injury cardiomyocyte (CM) loss can lead to myocardial dysfunction and failure. Although neonatal mammalian hearts can regenerate, the underlying molecular mechanisms remain elusive. Herein, comparative transcriptome analyses identify adherens junction protein N-Cadherin as a crucial regulator of CM proliferation/renewal. Its expression correlates positively with mitotic genes and shows an age-dependent reduction. N-Cadherin is upregulated in the neonatal mouse heart following injury, coinciding with increased CM mitotic activities. N-Cadherin knockdown reduces, whereas overexpression increases, the proliferation activity of neonatal mouse CMs and human induced pluripotent stem cell-derived CMs. Mechanistically, N-Cadherin binds and stabilizes pro-mitotic transcription regulator β-Catenin, driving CM self-renewal. Targeted N-Cadherin deletion in CMs impedes cardiac regeneration in neonatal mice, leading to excessive scarring. N-Cadherin overexpression, by contrast, promotes regeneration in adult mouse hearts following ischemic injury. N-Cadherin targeting presents a promising avenue for promoting cardiac regeneration and restoring function in injured adult human hearts.